Isolation, Characterization and Identification of Bacteria associated with Mucus of Acropora cervicornis Coral from Bidong Island, Terengganu, Malaysia - M, Kalimutho; Ahmad, Aziz; Kassim, Zaleha (Malaysian Journal of Science, 2007)
Marine bacteria associated with mucus of Acropora cervicornis coral of Bidong Island were successfully isolated and cultured on sucrose sea water agar (SSW). The bacteria were characterized by using selective culture media and biochemical assays. Four major groups of bacteria were obtained, Î³-proteobacteria, Î±-proteobacteria, high G+C gram positive bacteria, CFB group and unknowns. The coral mucus-associated bacteria strains were identified as Pantoea dispersa, Pseudomonas sp., Enterobacter agglomerans, Cadacea darisae, Serratia plymuthica, Citrobacter youngae, Erwinia herbicola, Vibrio sp., Klebsielle pneumonia subspecies ozanae, Aeromonas caviae, Alteromonas putrefaciens, Serratia sp., Alteromonas sp., Moraxella sp., Photobacterium sp., Yersinia bercovieri, Vibrio metschnikovii, Acinetobacter sp., Yersinia entrocolitica, Brucella sp., Micrococcus sp., Micrococcus varians, Micrococcus roseus, Actinomyces sp. and Flavobacterium sp.